Skeletal manifestations of stress in child victims of the Great Irish Famine (1845–1852): Prevalence of enamel hypoplasia, Harris lines, and growth retardation. Issue 1 (11th July 2014) - Geber, Jonny
ABSTRACT The Great Irish Famine of 1845–1852 is among the worst food crises in human history. While numerous aspects of this period have been studied by generations of scholars, relatively little attention has so far been given to the physiological impact it is likely to have had on the people who suffered and succumbed to it. This study examines the prevalence of enamel hypoplasia, Harris lines, and growth retardation in the nonadult proportion of a skeletal population comprising victims of the Famine who died in the workhouse in the city of Kilkenny between 1847 and 1851. The frequency of enamel hypoplasia in these children does not appear to have increased as a consequence of famine, although this fact is likely to be a reflection of the osteological paradox. Harris lines and growth retardation; however, were very prevalent, and the manifestation and age‐specific distribution of these may be indicators of the Famine experience. While there was no clear correlation in the occurrence of the assessed markers, the presence of cribra orbitalia displayed a significant relationship to enamel hypoplasia in 1‐ to 5‐year‐old children. While starvation, metabolic disorders and infectious diseases are likely to have greatly contributed to the manifestation of the markers, the psychosocial stress relating to institutionalization in the workhouse should not be underestimated as a substantial causative factor for skeletal stress in this population. Am J Phys Anthropol 155:149–161, 2014. © 2014 Wiley Periodicals, Inc.